Association of Mast Cell Burden and TIM-3 Expression with Recalcitrant Chronic Rhinosinusitis with Nasal Polyps. (September 2021) - Belsky, Michael A.; Corredera, Erica; Banerjee, Hridesh; Moore, John; Wang, Li; Kane, Lawrence P.; Lee, Stella E.
Objectives: Previous work showed that higher polyp mast cell load correlated with worse postoperative endoscopic appearance in patients with chronic rhinosinusitis with nasal polyps (CRSwNP). Polyp epithelial mast cells showed increased expression of T-cell/transmembrane immunoglobulin and mucin domain protein 3 (TIM-3), a receptor that promotes mast cell activation and cytokine production. In this study, CRSwNP patients were followed post-operatively to investigate whether mast cell burden or TIM-3 expression among mast cells can predict recalcitrant disease. Methods: Nasal polyp specimens were obtained via functional endoscopic sinus surgery (FESS) and separated into epithelial and stromal layers via enzymatic digestion. Mast cells and TIM-3-expressing mast cells were identified via flow cytometry. Mann-Whitney U tests and Cox proportional hazard models assessed whether mast cell burden and TIM-3 expression were associated with clinical outcomes, including earlier recurrence of polypoid edema and need for treatment with steroids. Results: Twenty-three patients with CRSwNP were studied and followed for 6 months after undergoing FESS. Higher mast cell levels were associated with earlier recurrence of polypoid edema: epithelial HR = 1.283 ( P  = .02), stromal HR = 1.103 ( P  = .02). Percent of mast cells expressing TIM-3 in epithelial or stromal layers was not significantly associated with earlier recurrence of polypoid edema. Mast cell burden and TIM-3+ expression were not significantly associated with need for future treatment with steroids post-FESS. Conclusions: Mast cell load in polyp epithelium and stroma may predict a more refractory postoperative course for CRSwNP patients. The role of TIM-3 in the chronic inflammatory state seen in CRSwNP remains unclear.